Pelatihan Desain Grafis Menggunakan Aplikasi Pixellab di Desa Sidomulyo (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2022)
Village teenagers are a group where they are the objects of events in the village where they live. Graphic design is a communication process using visual elements, such as typography, photography, and illustrations that are intended to create a perception of a message being conveyed. In general, graphic designers make extensive use of images, photos, symbols, and various forms of language and visual elements. In this community service activity, we will help village teenagers develop their potential to get job opportunities in the design field to strengthen their economy and productivity. Graphic design training can provide basic graphic design skills to village teenagers to be able to create publication media. The purpose of this program is to provide knowledge about graphic design to teenagers, provide knowledge about coloring in making a design, change consumer behavior in teenagers regarding smartphone use, and build relationships between teenagers. The method used for community mapping is the Service Learning (SL) method. According to Seifer, Service Learning is a teaching method that combines community service with academic learning objectives. From the questionnaire data that has been distributed, 60% of the total respondents stated that they were satisfied with the graphic design training with the pixellab application.